Gender in the Workplace : a Case Study Approach. - DeLaat, Jacqueline (SAGE Publications, 2007)
This brief collection of cases is designed to help students and employees gain a hands-on understanding of gender issues in the workplace and to provide the necessary tools to handle those issues. Based on actual legal cases, nationally reported incidents, and personal interviews, the case studies in Gender in the Workplace address the range and types of gender issues in the workplace. Completely revised and updated, this Second Edition provides a more international dimension to reinforce the varying impact of different cultures on gender issues.